Drought characterization and potential of nature-based solutions for drought risk mitigation in Eastern Ethiopia - Sintayehu, Dejene Workeneh; Kassa, Asfaw Kebede; Tessema, Negash; Girma, Bekele; Alemayehu, Sintayehu; Hassen, Jemal Yousuf (MDPI, 2023)
Drought is one of the challenges in Ethiopia that affects the agricultural production. Ecosystems can mitigate the effects of climate-related hazards including drought. For this reason, nature-based solutions (NbS) are becoming more prominent to manage climate-related impacts in developing countries; however, there is still limited empirical evidence, which would inform NbS policy and practices. Thus, the aim of this study was to characterize droughts in Eastern Ethiopia (the case of Erer Sub-basin) and assess the effectiveness of various NbS for drought. The temporal changes in soil moisture deficit index (SMDI) (agricultural drought) and standard precipitation evapotranspiration index (SPEI) (meteorological drought) at various timescales (1, 3, and 6 months) between 1981 and 2020 were analyzed. Qualitative analysis was used to categorize and evaluate the effectiveness of NbS to mitigate drought risk by adopting a Living Labs approach. Overall, the study revealed that droughts showed an increasing trend with more frequency, longevity, and severity. The drought analysis results showed that SPEI’s variants were less reliable than SMDI0–5 and SMDI5–100. With an increase in rainfall, SPEI showed stronger relationships with SMDI0–5 at one and two-month delays between May and July. SPEI and SMDI5–100 performed better in terms of capturing actual drought occurrences than SMDI0–5. The results of focus group discussions (FGD) suggested NbS such as habitat restoration, structural restoration, reforestation, rehabilitation, revegetation, land enclosures, conservancies, and locally managed areas have been practiced as a strategy to manage drought risks. Overall, the study indicated that a new, comprehensive approach through nature-based solutions to reduce the risk of drought is urgently needed.